Learning in virtual worlds : research and applications - Gregory, Sue; Lee, Mark J. W., 1981-; Dalgarno, Barney; Tynan, Belinda (Issues in distance education series., 2016)
In this authoritative collection, a team of international experts outline the emerging trends and developments in the use of 3D virtual worlds for teaching and learning.